Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1093/fampra/10.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Counselling Patients to Make Lifestyle Changes: The Role of Physician Self-Efficacy, Training and Beliefs About Causes

Abstract: Three factors that might help explain the extent to which physicians counsel patients to quit smoking and lose weight were examined: counselling self-efficacy, training in behaviour change and beliefs about causes of smoking and being overweight. More aggressive counselling was defined as counselling more patients per month and following up on counselling recommendations. Questionnaires were returned by 85 health maintenance organization physicians. As predicted, physicians with a stronger sense of counselling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…This also happens to be the step in which the psychiatrists had the strongest efficacy expectations. Research has found that physicians with a greater sense of self-efficacy for prevention activities resulted in more frequent physician counseling (Thompson, Schwankovsky, & Pitts, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This also happens to be the step in which the psychiatrists had the strongest efficacy expectations. Research has found that physicians with a greater sense of self-efficacy for prevention activities resulted in more frequent physician counseling (Thompson, Schwankovsky, & Pitts, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Further, being screened for one type of cancer, such as colorectal cancer, may also provide an opportunity to promote adherence to other cancer screenings (60). Incorporating such an integrative approach in primary care and other health care settings where colorectal cancer screening is conducted will require overcoming challenges at multiple levels of the health care system, including time constraints (61), reimbursement for the delivery of behavioral risk factor assessment and intervention (62), the availability of appropriate assessment tools for multiple behavioral risk factors (63), and provider willingness and ability to engage in behavior change counseling (64). Some of these challenges may be overcome, or minimized, by combining organizational practice changes (65), with the use of information technology (66) to streamline and automate the delivery of colorectal cancer preventive services.…”
Section: Discussionmentioning
confidence: 99%
“…• perception of own ability to influence the lifestyle and eating habits of patients with health problems (which is a self-efficacy factor) [16,[18][19][20];…”
Section: Dependent Variable "Extent Of Nutrition Education and Informmentioning
confidence: 99%